Metformin improves Mycobacterium avium infection by strengthening macrophage antimicrobial functions - Mediaas, Sindre Dahl; Haug, Markus; Louet, Claire; Wahl, Sissel Gyrid Freim; Gidon, Alexandre; Flo, Trude Helen (Frontiers in Immunology, 2024)
IntroductionThe incidence and prevalence of infections with non-tuberculous mycobacteria such as Mycobacterium avium (Mav) are increasing. Prolonged drug regimens, inherent antibiotic resistance, and low cure rates underscore the need for improved treatment, which may be achieved by combining standard chemotherapy with drugs targeting the host immune system. Here, we examined if the diabetes type 2 drug metformin could improve Mav-infection.MethodsMetformin was administered to C57BL/6 mice infected intranasally with Mav and C57BL/6 mice were infected intranasally with Mav and treated with metformin over 3 weeks. Organ bacterial loads and lung pathology, inflammatory cytokines and immune cell profiles were assessed. For mechanistic insight, macrophages infected with Mav were treated with metformin alone or in combination with inhibitors for mitochondrial ROS or AMPK and assessed for bacterial burden and phagosome maturation.Results and discussionThree weeks of metformin treatment significantly reduced the lung mycobacterial burden in mice infected with Mav without major changes in the overall lung pathology or immune cell composition. Metformin treatment had no significant impact on tissue inflammation except for a tendency of increased lung IFNγ and infiltration of Mav-specific IFNγ-secreting T cells. Metformin did, however, boost the antimicrobial capacity of infected macrophages directly by modulating metabolism/activating AMPK, increasing mitochondrial ROS and phagosome maturation, and indirectly by bolstering type I immunity. Taken together, our data show that metformin improved the control of Mav-infection in mice, mainly by strengthening antimicrobial defenses in macrophages, and suggest that metformin has potential as an adjunct treatment of Mav infections.